We have a circle represented by the equation:
![(x-4)^2+(y-2)^2=7^2=49](https://img.qammunity.org/2023/formulas/mathematics/college/50q1l79arhu690x31awbft00u0o988v1gm.png)
Any point that satisfy the equation of the circle lies in the circumference of the circle.
We can test each point by replacing the values of x and y in the equation by the coordinates of the point.
A) (-1,4)
![\begin{gathered} (-1-4)^2+(4-2)^2=49 \\ (-5)^2+2^2=49 \\ 25+4=49 \\ 29\\eq49 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1sihm1w9bcv8xo7rz2q05rcxfamxeebmby.png)
The point (-1,4) does not lie in the circle.
B) (8,3)
![\begin{gathered} (8-4)^2+(3-2)^2=49 \\ 4^2+1^2=49 \\ 16+1=49 \\ 17\\eq49 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8vyzla4039cepav1dpftfdmg9yb015kt5p.png)
The point (8,3) does not lie in the circle.
C) (9,0)
![\begin{gathered} (9-4)^2+(0-2)^2=49 \\ 5^2+(-2)^2=49 \\ 25+4=49 \\ 29\\eq49 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qgyi6aq4ygwk1j40kny3fz1kvl086bsap3.png)
The point (9,0) does not lie in the circle.
D) (-2,2)
![\begin{gathered} (-2-4)^2+(2-2)^2=49 \\ (-6)^2+0^2=49 \\ 36+0=49 \\ 36\\eq49 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zhdyg651gk4pu1xtp8v9mj28b8o331itrk.png)
The point (-2,2) does not lie in the circle.